Type-C esophageal atresia with double distal fistula (IIIb13) - César Ramírez-Martínez; Alejandro Peñarrieta-Daher; Mario Peña-García; Jaime Penchyna-Grub; Gustavo Teyssier-Morales; Karla Muñoa-Carcamo; Jaime Nieto-Zermeño; Raúl Villegas-Silva; Cristian Zalles-Vidal (Elsevier, 2020)
Esophageal atresia (EA) is the most frequent congenital anomaly of the esophagus. According to Gross Classification, type-C esophageal atresia is the most common type. The Atlas of Esophageal Atresia by Kluth describes multiple variations of defects in EA. We present a female baby of 36 weeks' gestation, with IIIb13 esophageal atresia, an extremely rare subtype of type-C EA. During pre-surgical bronchoscopy, we observed the presence of a double fistula, which was confirmed in the surgery. The first fistula between trachea and esophagus, and the second fistula between right main bronchus and esophagus, both in the distal esophagus. We made an esophageal anastomosis preserving the total length of the distal esophagus. This is the first report in over 20 years, and the third in the literature. The patient had a satisfactory evolution. After five months of follow-up the patient eats by suction only, with adequate weight gain, without suggestion of stenosis or gastroesophageal reflux.